Effects of maternal depression and prenatal SSRI exposure on executive functions and susceptibility to household chaos in 6-year-old children: prospective cohort study. Issue 5 (September 2020) - Dhaliwal, Gurpreet; Weikum, Whitney M.; Jolicoeur-Martineau, Alexia; Brain, Ursula; Grunau, Ruth E.; Oberlander, Tim F.
Abstract : Background: Maternal depressed mood during pregnancy may shape a child's adaptation to their environment and engagement in goal-directed behaviour such as executive functions. Whether everyday household context also alters executive functions in children with prenatal selective serotonin reuptake inhibitor (SSRI) antidepressant exposure remains to be determined. Aims: To examine the impact of prenatal depressed maternal mood and SSRI exposure on child executive functions and to determine whether these exposures shape a susceptibility to household chaos. Method: A prospective cohort study of mothers and their children (118 mother–children dyads (47 SSRI-exposed, 71 non-exposed)) followed from the second trimester to 6 years. Regression models examined relationships between maternal depressed mood and household chaos on maternal report of child executive functions. Competitive-confirmatory regression models examined whether children were susceptible to household chaos or were positively influenced by less chaos. Results: Prenatal SSRI exposure, third-trimester maternal depressed mood and household chaos in a three-way interaction were associated with executive functions within a model of differential susceptibility. When household chaos was low, children of non-prenatally depressed mothers had better executive function than children of prenatally depressed mothers, regardless of whether the mothers were SSRI-treated. However, when household chaos was high, SSRI-exposed children of mothers who were not depressed during pregnancy had poorer executive functions at 6 years of age compared with SSRI-exposed children whose mothers were symptomatic during pregnancy. Conclusions: The impact of household chaos depended on whether mothers were prenatally depressed and whether mothers were SSRI-treated.